1989
DOI: 10.1159/000460912
|View full text |Cite
|
Sign up to set email alerts
|

ABH and Related Histo-Blood Group Antigens; Immunochemical Differences in Carrier Isotypes and Their Distribution

Abstract: This review summarizes present knowledge of the chemistry of histo-blood group ABH and related antigens. Recent advances in analytical carbohydrate chemistry (particularly mass spectrometry and NMR spectroscopy) and the introduction of monoclonal antibodies (MoAbs) have made it possible to distinguish structural variants of histo-blood group ABH antigens. Polymorphism of ABH antigens is induced by; (i) variations in peripheral core structure, of which four (type 1, 2, 3 and 4) are known in man; (ii) variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
238
0
3

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(243 citation statements)
references
References 62 publications
2
238
0
3
Order By: Relevance
“…We did not analyze glycolipids in the ␤3GnT2 Ϫ/Ϫ mouse. However, we previously documented that only ␤3GnT5 can synthesize Lc 3 Cer and nLc 5 Cer, resulting in neolacto-series glycolipids, which contain polylactosamines (17). ␤3GnT5 is responsible for the synthesis of Lc 3 Cer in hematopoietic cells (17,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not analyze glycolipids in the ␤3GnT2 Ϫ/Ϫ mouse. However, we previously documented that only ␤3GnT5 can synthesize Lc 3 Cer and nLc 5 Cer, resulting in neolacto-series glycolipids, which contain polylactosamines (17). ␤3GnT5 is responsible for the synthesis of Lc 3 Cer in hematopoietic cells (17,24).…”
Section: Discussionmentioning
confidence: 99%
“…Polylactosamine containing repeats of the N-acetyllactosamine (LacNAc) unit (Gal␤1-4GlcNAc␤1-3)n is a fundamental structure of glycans carried on N-and O-glycans (2,3) and glycolipid (4). Human blood group i and I antigens are linear and branched polylactosamine structures, respectively (5,6).…”
mentioning
confidence: 99%
“…The a(l,2)fucosyltransferase that forms the H antigen, an essential precursor of the A and B antigens, plays a regulatory role in the tissue expression of the ABO antigens. Several lines of evidence have indicated that at least two a( 1,2)fucosyltransferases are present in human tissues [6, 71. One is the H-type FUTl-encoded a(l,2)fucosyltransferase, which regulates the expression of the H antigen mainly on erythrocyte membranes and the other is the secretortype FUT2-encoded a( 1,2)fucosyltransferase, which regulates the expression of the H antigen mainly in epithelial cells and body fluids such as saliva [4,5,[8][9][10]. FUTI, FUT2, and a FUT2 pseudogene (Secl) have been isolated [ll-131.…”
mentioning
confidence: 99%
“…Changes in expression of the class of cell surface carbohydrates called blood group antigens have been documented during tumour progression (reviewed in Clausen and Hakomori, 1989;Hakomori, 1996;King, 1994), and can have prognostic signi®cance (e.g. Miyake et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…ABH antigens are expressed on glandular epithelia, neurones and in exocrine secretions, and are carried on N-or O-linked sugar modi®cations of glycoproteins and glycosphingolipids, or are present as free oligosaccharides (reviewed in Clausen and Hakomori, 1989;King, 1994). Only humans and certain primates carry ABH antigens on endothelial cells and on erythrocytes (Oriol et al, 1984), where in the latter case they have a histocompatibility function.…”
Section: Introductionmentioning
confidence: 99%